Application of Immunological and Swarm Intelligence Learning-Based Algorithm for Industrial Grade Computer Sales Prediction - Zhen-Yao Chen (Applied Artificial Intelligence)
This paper strives to raise the imitating effectiveness of radial basis function-based neural network (RNNet) through biological learning (BL) and swarm intelligence (SI) optimization algorithms. Latter, the artificial immune system (AIS) and particle swarm optimization (PSO) algorithms are utilized for RNNet to regulate. The proposed synthesis of AIS-inspired and PSO-inspired (SAIPS) algorithm incorporates the complementary development and prospecting abilities to realize optimized resolution. The attribute of population variation has shown high frequency to meet the global optimum to replace local optimum being restricted and outperforms in five standard nonlinear trial functions. The experimental results have represented that the consolidation of AIS-inspired and PSO-inspired algorithms is an outstanding approach and therefore a hybrid algorithm is proposed, which aims to obtain an expression that can cultivate optimum precision among related algorithms in this research. The algorithm then evaluates results from five standard inspections and an empirical industrial grade computer (IgC) sales prediction instance in Taiwan, which reveals that the proposed SAIPS algorithm exceeds the performance among related algorithms as well as the relevant auto-regressive integrated moving average (ARIMA) models in terms of accuracy and time spent.